(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the maternal factors involved with low birth weight (LBW) newborns. Study Design: Cross sectional study. Place and Duration of Study: This was a Multi-centric study conducted at three centers i.e. Department of Pediatrics Medicine, Bahawal Victoria Hospital Bahawalpur, Department of Pediatrics, Ghulam Muhammad Mahar Medical College Hospital, Sukkur, and Department of Pediatrics, Unit-II, Children Hospital Chandka Medical College / SMBBMU, Larkana from December 2018 to May 2019. Materials and Methods: A total of 335 single alive LBW babies delivered, referred, or reported at study centers, were included. All mothers of newborns were aged 18 to 35 years. Newborn’s data including gender and weight were recorded. Maternal data included age, gestational age, parity status, details of antenatal visits and any sort of complications. Mother’s data such as pregnancy induced hypertension (PIH (BP systolic more than 140mm of Hg and diastolic more than 90mm of Hg), anemia (hemoglobin less than 10mg/dl) during pregnancy or antepartum hemorrhage (APH) were also noted. Results: There were 170 (50.7%) male and 175 (49.3%) female newborns. IUGR was reported in 193 (57.6%) newborns while there were 142 (42.4%) preterm newborns Mean weight of the newborns was recorded as 2238 grams with a standard deviation of 327 grams. Majority of the newborns, 276 (82.4%) had birth weight between 2000 to 2500 grams, belonged to rural areas 197 (58.8%). Majority of the mothers, 261 (77.9%) were aged 20 to 29 years, 178 (53.1%) had regular antenatal visits (> 3 visits), 198 (59.1%) were multipara and 170 (50.7%) had anemia during pregnancy. Conclusion: High frequency of maternal factors such as multiparity, anemia, low to medium socioeconomic status, rural area of residence, irregular medical check-ups and age from 20 to 30 years, were noted amongst mothers of LBW newborns.